Análise da concentração de elementos potencialmente tóxicos em hortaliças cultivadas de modo convencional, hidropônico e orgânico - Silva, Victor Dubas da (Universidade Federal de São Carlos, 2022)
In search of a better quality of life, it is currently common to look for organic products, which tend to be seen as healthier, one of the reasons being the possibility of them having less contaminants. Amongst the main contaminants are the potentially toxic elements (PTEs), as, for instance, cadmium, copper, chromium and lead. Motivated by the risks posed by the consumption of food contaminated with PTEs and the availability of vegetables grown by different farming methods, this study analysed the concentrations of Al, Ba, Cd, Co, Cr, Cu, Fe, K, Mn, Mo, Ni, Pb, Sr and Zn in curly and smooth lettuce, collard greens, escarole and rocket grown by conventional farming, hydroponics and organic farming, aiming to investigate possible relations between the concentrations of PTEs and the farming methods. The samples were obtained in the region of Sorocaba – SP in local commerce, and the concentrations were determined by microwave plasma atomic emission spectroscopy (MPAES). Higher concentrations of Al, Ba and Fe were observed on vegetables from conventional farming (C), when compared to those from organic farming (O), and the latter higher than those from hydroponics (H) (trend C > O > H). K, Pb and Zn showed the trend O > C; Sr: C > O = H; Mn: C > O; Mo was present in a lower concentration on vegetables from conventional farming; and for Cr and Cu no tendencies were observed. Cd, Co and Ni concentrations were below the limit of detection in most samples and, therefore, it was not possible to find any trend for these elements. In this context, for the studied samples, it was not possible to affirm that a given farming method favours higher or lower concentrations of the analysed elements in general. However, the knowledge about PTEs concentrations on vegetables is fundamental to the monitoring of these species on the environment, as it is for the maintenance of a food quality control.
Analysis of the concentration of potential elements toxics in conventionally grown vegetables, hydroponic and organic
Keywords: Contaminação alimentar; Alimentação saudável; Cultivo de vegetais; Agricultura orgânica; Elementos potencialmente tóxicos; Food contamination; Healthy eating; Vegetable farming; Organic farming; Potentially toxic elements; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ANALISE DE TRACOS E QUIMICA AMBIENTAL